COMPARISON OF PROCESSED VEHICLE WASH WASTE USING SILICA SAND AND ACTIVATED CARBON MEDIA - Arry Setiawan; Charles Situmorang (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2023)
Human activities are generating a lot of waste that can degrade the quality of the environment, oneof which is the activity of washing motorcycles and cars. Especially in the city of Karachi is growingrapidly and increasing the number of vehicles. So that the proliferation of motor and car washactivities. Therefore the need for handling of waste disposal of motor and car washing. One of thewastewater treatment of motor and car wash discharges is by filtration process with many usablemedia. For this writing the author uses silica sand media and activated carbon used in filtrationreactor. The goal is to reduce the levels of BOD, COD, TSS and pH. In this study the authors use areactor filtration by comparing two media between silica sand media and activated carbon with eachmedia distinguished height of 10 cm, 15 cm and 20 cm. The purpose of the treatment is to knowwhich media is better at lowering levels of pollution. In addition the authors want to know whetherthere is an influence of height in lowering levels of pollutants.